Falia‘s Ke-kaghati-an in Muna Speech Community From the Ecolinguistic Perspective - Nirmalasari; Aron Meko Mbete; I Wayan Simpen; Anak Agung Putu Putra (e-Journal of Linguistics, 2019)
This paper explained falia ‘taboo’ in kaghati in the Muna Speech Community (MSC)from the ecolinguistic perspective. The kite ‘kaghati’ is one type of the traditional games and a tribalcultural product in MSC which still exists and remains maintained. The forms of interaction,interrelation, and the interdependence in MSC with the natural and socio-cultural environments arerecorded in falia’s ke-kaghati-an.The problem in this paper is to answer the question what expressionin falia’s ke-kaghati-an is used to express environment in MSC. The purpose of this paper is todescribe and analyze the falia expressions found in ke-kaghati-an’s environment. This research isclassified as a qualitative descriptive study as it describes the phenomena of falia expressions andenvironmental knowledge, especially the ones currently used in ke-kaghati-an’s environment, andthe source of natural data as a manifestation of the Muna's socio-cultural-ecological life.Falia’s ke-kaghati-an is such a magical expression of magical value that MSC, especially the kaghatimaker, feels afraid of breaking it.The expression of falia’s ke-kaghati-an teaches the belief in God,gratitude, balance of life, discipline, justice, honesty, orderliness, beauty, tolerance, and mutualrespect. Falia is one way in which MSC shows their adherence to the local wisdom values, especiallywith regard to the environmental conservation that has been inherited from the ancestors since a longtime ago. Conservation of the wealth of the expression of falia in MSC is very important, for both thesustainability of the Muna language and the conservation of kaghati with its traditions and culture,which is preserved in the meaning and cultural values of the past heritage as part of itspersonalidentity, especially for the younger generation.